HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MENJALANKAN DIET HIPERTENSI DI PUSKESMAS KOTA KUALA SIMPANG ACEH TAMIANG TAHUN 2019 - Nora Hayani; Azwarni Azwarni; Eva Sulistiany; Zulkarnain Zulkarnain; Elfida Elfida (Jurnal Inovasi Penelitian, 2021)
Hypertension is a big and serious problem, in addition to its high prevalence and tends to increase every year, also because of the seriousness of this disease which causes other diseases such as heart disease, stroke and even sudden death. Hypertension diet is one of the effective non-pharmacological strategies to modify and control blood pressure, but patients must be completely obedient in implementing a hypertension diet. The purpose of this study was to determine the relationship between knowledge and family support with adherence to a hypertension diet at the Kuala Simpang City Health Center, Aceh Tamiang Regency in 2019. This type of research was descriftive analytic with a cross sectional study design where the independent variable and the dependent variable were obtained at the same time. The population in this study were 43 hypertensive patients with accidental sampling technique. The results showed that there was a relationship between knowledge and adherence to diet in hypertensive patients. The results of the Chi-Square test at the 95% confidence level obtained p value = 0.003 (p<0.05), there is a relationship between family support and dietary compliance in patients with hypertension obtained p-value = 0.001 (p<0.05). It is hoped that hypertensive patients will adhere to a hypertension diet so that blood pressure can be controlled.